6-7n=29 would be your answer
<span>Simplifying
6(x + -1) = 9(x + 2)
Reorder the terms:
6(-1 + x) = 9(x + 2)
(-1 * 6 + x * 6) = 9(x + 2)
(-6 + 6x) = 9(x + 2)
Reorder the terms:
-6 + 6x = 9(2 + x)
-6 + 6x = (2 * 9 + x * 9)
-6 + 6x = (18 + 9x)
Solving
-6 + 6x = 18 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
-6 + 6x + -9x = 18 + 9x + -9x
Combine like terms: 6x + -9x = -3x
-6 + -3x = 18 + 9x + -9x
Combine like terms: 9x + -9x = 0
-6 + -3x = 18 + 0
-6 + -3x = 18
Add '6' to each side of the equation.
-6 + 6 + -3x = 18 + 6
Combine like terms: -6 + 6 = 0
0 + -3x = 18 + 6
-3x = 18 + 6
Combine like terms: 18 + 6 = 24
-3x = 24
Divide each side by '-3'.
x = -8
Simplifying
x = -8</span>
Answer:
It's 2
Step-by-step explanation:
X is 2 because if you multiply two by two you get 4
Answer:
Ok.
Step-by-step explanation:
What is your question?
well, if Nathan has 15 million dollars and buys 2 bags and 3 books and if each bag is 2 million you would do 15 minus 2 and when you get the answer you would minus 10 dollars off of that and then do 10 times that number.
I hope you understand what I'm saying if not pls ask for help.